Molecular packing structure of fibrin fibers resolved by X-ray scattering and molecular modeling. Issue 35 (17th August 2020) - Jansen, Karin A.; Zhmurov, Artem; Vos, Bart E.; Portale, Giuseppe; Hermida-Merino, Daniel; Litvinov, Rustem I.; Tutwiler, Valerie; Kurniawan, Nicholas A.; Bras, Wim; Weisel, John W.; Barsegov, Valeri; Koenderink, Gijsje H.
Abstract : The blood clotting protein fibrin has extraordinary elastomeric properties due to its hierarchical structure. SAXS is combined with computational molecular modeling, providing insight in fibrin elasticity and guidelines for designing new polymers.  Abstract : Fibrin is the major extracellular component of blood clots and a proteinaceous hydrogel used as a versatile biomaterial. Fibrin forms branched networks built of laterally associated double-stranded protofibrils. This multiscale hierarchical structure is crucial for the extraordinary mechanical resilience of blood clots, yet the structural basis of clot mechanical properties remains largely unclear due, in part, to the unresolved molecular packing of fibrin fibers. Here the packing structure of fibrin fibers is quantitatively assessed by combining Small Angle X-ray Scattering (SAXS) measurements of fibrin reconstituted under a wide range of conditions with computational molecular modeling of fibrin protofibrils. The number, positions, and intensities of the Bragg peaks observed in the SAXS experiments were reproduced computationally based on the all-atom molecular structure of reconstructed fibrin protofibrils. Specifically, the model correctly predicts the intensities of the reflections of the 22.5 nm axial repeat, corresponding to the half-staggered longitudinal arrangement of fibrin molecules. In addition, the SAXS measurements showed that protofibrils within fibrin fibers have a partially ordered lateral arrangement with a characteristic transverse repeat distance of 13 nm, irrespective of the fiber thickness. These findings provide fundamental insights into the molecular structure of fibrin clots that underlies their biological and physical properties.